Clinical Pro?le of Neonatal Early Onset Sepsis: A Study on the Current Scenario - Kiran C Pankaj; Sristi Ganguly; Manas R Upadhyay (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Neonatal early onset sepsis remains to be a challenge in India, owing to its variable presentation, diagnostic difficulty and high fatality. An attempt needs to be made to study its clinical profile for easy identification of such babies, with new antibiotic guidelines formulated based on current microorganisms isolated. The aim of the study is to study the clinical profile of early onset sepsis in neonates in terms of      the risk factors, clinical factors and etiology, and ascertain factors associated with definite sepsis. Subjects and Methods: This hospital based cross-sectional study enrolled neonates with suspected early onset sepsis. Those with congenital anomalies, surgical conditions, gestation <28 weeks and birth weight <1kg excluded. Subjects were subjected to sepsis screen and blood culture, and their perinatal history recorded. Blood culture positive babies were considered to have definite sepsis. Data was analysed using Chi square with SPSS 18. Results: Among 300 babies enrolled, 70 babies had definite sepsis. The most common organism isolated was Klebsiella (27.1%) and Staphylococcus hemolyticus (21.4%), most showing sensitivity to Ampicillin and Gentamicin. Respiratory distress was the commonest presentation (71.3%). A significant association with definite sepsis was seen with prematurity (p =0.0026) and low birth weight (p =0.0052), perinatal risk factors namely premature rupture  of membranes (p =0.004), foul smelling liquor (p=0.016) and birth asphyxia (p-value=0.02). 28.3% had positive sepsis screen, which was significant (p = 0.001). Conclusion: Early onset sepsis needs prompt identification and treatment initiation, possible with aid of sepsis screen and high index of suspicion with certain perinatal risk factors and gestational age and birth weight.